Development of district health network management model to support transferring district health promoting hospital to local government organization in Saraburi Province - Suwannawong, Yodchai; Opassawas, Preecha (Journal of Medical and Public Health Region 4, 2022)
The purposes of this mixed-method research was study to development of district health network management model to support transferring district health promoting hospital to local government organization in saraburi province. The research was study during January – April 2021. The samples consisted of the executive and stakeholders of health network in Kaeng Khoi, Nong khae and SaoHai districts, selected by the purposive sampling and the simple random technique. The semi-structured interview and the questionnaire were constructed and used as tools for data collection; and the data were analyzed by using content analysis and descriptive statistics. It was found that the district health network management model to support transferring district health promoting hospital to local government organization in Saraburi province consisted of 5 components; (1) Conceptual: All collaborative for health and Network cooperation; (2) Principles: Raise awareness of leader, Building a network commitment, and Creating a participation culture; (3) Goals: Seamless health system, Smart health network, and Smart district health promoting hospital; (4) Process: Social understanding, Potential Readiness Assessment, Health network MOU, Establish a district health committee, Formulation of strategic health plans, Organize a public forum for health cooperation, Health network communication, and Monitoring and evaluation; and (5) Evaluation: Network participation, Health organization readiness, and Usefulness satisfaction. The beneficial conditions of model were Health leadership, Strong of health network, and Policy support. The model was considered high level in actually utility ( =4.57, S.D.=0.29) and feasibility ( =3.58, S.D.=0.71) could be applied to the context of the society in the community in Saraburi Province,